Structural and stress analysis - Megson, T. H. G. (Butterworth-Heinemann, 2000)
This book discusses the determination of the strength and stiffness of civil engineering structures determining the loads they will support before failure and the displacements the loads produce.
Previously published: London : Arnold ; New York : Halstead Press, 1996.
Keywords: Structural analysis (Engineering); Strains and stresses.; elektronické knihy; electronic books